What is a sarcoma ‘Specialist center’?: Multidisciplinary research finds an answer - Wilson, Roger; Reinke, Denise; van Oortmerssen, Gerard; Gonzato, Ornella; Ott, Gabriele; Raut, Chandrajit P.; Guadagnolo, B. Ashleigh; Haas, Rick L. M.; Trent, Jonathan; Jones, Robin; Pretorius, Lauren; Felser, Brandi; et al. (Cancers, 2024)
The management of sarcomas in specialist centers delivers significant benefits. In much of the world, specialists are not available, and the development of expertise is identified as a major need. However, the terms ‘specialist’ or ‘expert’ center are rarely defined. Our objective is to offer a definition for patient advocates and a tool for healthcare providers to underpin improving the care of people with sarcoma. SPAGN developed a discussion paper for a workshop at the SPAGN 2023 Conference, attended by 75 delegates. A presentation to the Connective Tissue Oncology Society (CTOS) and further discussion led to this paper. Core Principles were identified that underlie specialist sarcoma care. The primary Principle is the multi-disciplinary team discussing every patient, at first diagnosis and during treatment. Principles for optimal sarcoma management include accurate diagnosis followed by safe, high-quality treatment, with curative intent. These Principles are supplemented by Features describing areas of healthcare, professional involvement, and service provision and identifying further research and development needs. These allow for variations because of national or local policies and budgets. We propose the term ‘Sarcoma Intelligent Specialist Network’ to recognize expertise wherever it is found in the world. This provides a base for further discussion and local refinement.
Gesehen am 28.11.2024